Reconsidering the Declaration of ‘Crisis’ While Living through One (Medicine Anthropology Theory, 2022)
What counts as a ‘crisis’? How do we determine an ‘emergency’? Who gets to do so, and what exactly is at stake? Scholarly examinations of ‘crises’, including, most notably, seminal work by Janet Roitman (2013), frequently underscores how the ‘crisis imaginary’ is employed to rapidly and unjustifiably expand State power. Certainly, State responses to the COVID-19 pandemic have amply demonstrated this critique, as was noted early on by both Agamben (2020) and Chomsky (2020). Nonetheless, regardless of its political manipulations, crisis can also be understood as a phenomenological state, as there exist moments during which we collectively experience being plunged into a radically different time-space that is perhaps best conceptualised as a ‘collective critical event’. Such ‘extraordinary’ times have been denoted as events beyond the scope of narration (Briggs 2003); ‘failure[s] of the grammar of the ordinary’ (Das 2007); or moments of incredulity that surpass our capacities of narration. By focusing on the languaging of the COVID-19 pandemic in Aotearoa/New Zealand, this Position Piece grapples with how to reconcile the insights offered by critiques of the political deployment of claims of ‘crises’ with anthropological and other phenomenological accounts of experiences of moments of profound upheaval.